Autotomy, tail regeneration and jumping ability in Cape dwarf geckos (Lygodactylus capensis)(Gekkonidae) - Fleming, P.; Bateman, Bill (Universiteit Stellenbosch * Department of Botany and Zoology, 2012)
Many studies have examined the effect of caudal autotomy on speed and behaviour of lizardsescaping over horizontal surfaces, but there have been few studies on lizards escaping oververtical surfaces and, in particular, species that jump between surfaces.We examined jumpingby the Cape dwarf gecko (Lygodactylus capensis) in terms of individuals’ varying states of tailautotomy and regeneration. Although longer jumps were less likely to be successful (i.e. theanimal would not successfully grip the surface and fell to the ground), there was no differencein the distance over which animals with full and partial tails would attempt to jump. Bothrecently autotomized individuals and individuals with intact tails successfully jumped up tonine times their body length (snout–vent length). The jumping ability of L. capensis wastherefore clearly not negatively impaired by tail loss, presumably because the geckos are usingtheir hind legs to propel their jump. Their tails may, however, be important to control theirlanding as well as their locomotion on vertical surfaces. The high observed frequency of tailloss, coupled with rapid and complete regeneration (including the scansorial tail tip), suggeststhat caudal autotomy is an important survival tactic in this species.